2020
DOI: 10.1021/acssuschemeng.0c05065
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Magnetic MIP-Based SERS Sensors for Selective, Sensitive, and Reliable Detection of Paclobutrazol Residues in Complex Environments

Abstract: In this work, a molecularly imprinted polymer (MIP)-based SERS sensor for selective, sensitive, quantitative, and recyclable detection of paclobutrazol residues in complex environments has been proposed. In this strategy, Fe3O4@SiO2–Au@Ag (FSAA) nanocomposites with tunable Au@Ag interparticle gaps are constructed. Then, by tuning the Au@Ag nanogaps and investigating the SERS enhancement mechanism of FSAA, we achieve the optimal SERS substrate, FSAA-40. After combining with MIPs, we can selectively detect paclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 52 publications
0
19
0
3
Order By: Relevance
“…This tedious process is not only unsuitable for in-field analysis, but also risks introducing contamination and dilutes the analyte. Although it has been demonstrated that colloidal dispersions or pastes of enhancing nanoparticles can be physically deposited onto complex sample surfaces for in-situ analysis, 75,76 this approach is unsuitable for analyzing precious samples, such as artworks, or samples where the spatial distribution of the analytes holds important information, such as forensic fingerprint samples. A more ideal approach for analyzing chemical compounds on complex surfaces with SERS is to use flexible enhancing substrates, which are typically composed of exposed enhancing nanoparticles sitting on the surface of flexible and robust polymeric substrate materials.…”
Section: Flexible Sers Substrates For the Analysis Of Chemical Residues On Complex Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…This tedious process is not only unsuitable for in-field analysis, but also risks introducing contamination and dilutes the analyte. Although it has been demonstrated that colloidal dispersions or pastes of enhancing nanoparticles can be physically deposited onto complex sample surfaces for in-situ analysis, 75,76 this approach is unsuitable for analyzing precious samples, such as artworks, or samples where the spatial distribution of the analytes holds important information, such as forensic fingerprint samples. A more ideal approach for analyzing chemical compounds on complex surfaces with SERS is to use flexible enhancing substrates, which are typically composed of exposed enhancing nanoparticles sitting on the surface of flexible and robust polymeric substrate materials.…”
Section: Flexible Sers Substrates For the Analysis Of Chemical Residues On Complex Surfacesmentioning
confidence: 99%
“…74 copyright 2016 The Royal Society of Chemistry and ref. 75, copyright 2020 American Chemical Society. cellulose and cotton, which are infused with plasmonic nanoparticles.…”
Section: Flexible Sers Substrates For the Analysis Of Chemical Residues On Complex Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a small number of hot spots were generated between the Cu 2 O shell and Ag nanocrystals. The SERS signal intensity is closely related to the number of hot spots in SERS substrates 38 . When the number of Ag nanocrystals on the Cu 2 O shell increased, the SERS signal intensity increased.…”
Section: Sers Activity Analysismentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS), as one of the most powerful detection tools in chemical , and biochemical analyses, has been arousing extensive attention for its high sensitivity, label-free, and fingerprint identification. , In addition, SERS is recognized as a simple, nondestructive and nonpretreatment method, so its application is prioritized for rapid on-site screening. For this reason, the synthesis of novel and efficient SERS substrates is critical to food safety assessment and environmental monitoring.…”
Section: Introductionmentioning
confidence: 99%